Pengembangan E-Module Mata Pelajaran Ilmu Pengetahuan Alam Pokok Bahasan Interaksi Makhluk Hidup dengan Lingkungannya - Reny Samiasih; Sulton; Henry Praherdhiono (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2017)
The purpose of this development is to produce an e-module product that is feasible and valid as an effective learning resource and is able to improve student learning outcomes in junior high school science subjects, the subject of the interaction of living things with their environment. The results show that this e-module is valid. and suitable for use in the individual learning process and shows that this e-module is able to improve student learning outcomes, especially in the material of the interaction of living things with their environment.